Assessing Effectiveness of Google Classroom: Sankalchand Patel University Student’s Perceptions - Dr. Tushar Brahmbhatt (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2020)
The technological development has greatly influenced the world of education, especially higher education. However, many educators have been unable to figure out which of the many available technological tools best suit their classroom practices. Google classroom is a free web service, providing a collaborative tool allowing users to create virtual classrooms. It has gained a remarkable popularity within a very short period of time. The main purpose of the study is to assess the university students’ perception on the effectiveness of Google Classroom. A qualitative research design was employed in the present study. The sample of the study, which uses semi-structured interview method, consists of 20 higher education students of Gujarat who have been studying, taking the examinations and submitting their assignments using Google Classroom for at least two semesters during the severe COVID 19 situation in Gujarat (India). A comprehensive analysis by coding and categorizing the data through NVivo has been placed of the data acquired. Findings revealed that Google Classroom has significant impact on teaching-learning methodology. The responses of the students indicate that is user-friendly. Further studies can be undertaken by taking the perspective of the academicians into account.